The endocrine influence on the bone microenvironment in early breast cancer. Issue 12 (December 2016) - Wilson, Caroline; Brown, Hannah; Holen, Ingunn
Abstract : Multiple factors influence the survival of disseminated breast tumour cells (DTCs) in bone. Whereas gene signature studies have identified genes that predict a propensity of tumours to metastasise to bone, the bone environment is key in determining the fate of these tumour cells. Breast cancer cells locate to specific niches within the bone that support their survival, regulated by host factors within the bone microenvironment including bone cells, cells of the bone micro vasculature, immune cells and the extracellular matrix. Reproductive endocrine hormones that affect bone and clinical studies across the menopausal transition have provided comprehensive understanding of the changes in the bone microenvironment during this time. Menopause is characterized by a decrease in ovarian oestradiol and inhibins, with an increase in pituitary follicle-stimulating hormone and this review will focus on the role of these three hormones in determining the fate of DTCs in bone. Both in vivo and clinical data suggest that premenopausal bone is a conducive environment for growth of breast cancer cells in bone. Adjuvant cancer treatment aims to reduce the risk of tumour recurrence by affecting DTCs. Drugs targeting the bone resorbing osteoclasts, such as bisphosphonates, have therefore been evaluated in this setting. Both preclinical and adjuvant clinical studies have shown that bisphosphonates' ability to decrease tumour growth in bone is influenced by the levels of endocrine hormones, with enhanced effects in a postmenopausal bone microenvironment. The challenge is to understand the molecular mechanisms behind this phenomenon and to evaluate if alternative adjuvant bone-targeted therapies may be effective in premenopausal women.